2022
DOI: 10.1007/s10753-022-01672-7
|View full text |Cite
|
Sign up to set email alerts
|

Ti Ions Induce IL-1β Release by Activation of the NLRP3 Inflammasome in a Human Macrophage Cell Line

Abstract: The aim of the present study was to investigate whether titanium (Ti)-induced release of interleukin (IL)-1β acts through the assembly of the NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome. In addition, we examined whether particulate Ti or TiO2 activates the same intracellular pathways with the assembly of the NLRP3 inflammasome as Ti ions. Ti ions are known to induce IL-1β maturation and release by the formation of metal–protein aggregates. Wild-type THP-1 (wt.) cells and NLRP3− and ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Although regarded as being biocompatible, commercial grade titanium is not fully inert. Titanium can act as an abiotic stimulus to macrophages and activate the release of the NLRP3 inflammasome complex assembly [112]. Inflammation also impairs osteoblast attachment and function, and a pro-osteoclastic phenotype has been described on infected implant surfaces [113].…”
Section: Wound Healing In the Presence Of A Foreign Body Results In S...mentioning
confidence: 99%
“…Although regarded as being biocompatible, commercial grade titanium is not fully inert. Titanium can act as an abiotic stimulus to macrophages and activate the release of the NLRP3 inflammasome complex assembly [112]. Inflammation also impairs osteoblast attachment and function, and a pro-osteoclastic phenotype has been described on infected implant surfaces [113].…”
Section: Wound Healing In the Presence Of A Foreign Body Results In S...mentioning
confidence: 99%
“…In addition, nickel ions were shown to bind directly to CXCL4, an inflammatory chemokine, and exacerbate skin inflammation in a murine model of nickel-induced CHS using LPS as an adjuvant 31) . On the other hand, although the direct recognition mechanism of titanium is unknown, both titanium ions and nanoparticles were reported to induce cellular activity [7][8][9][10][11][12][13] . In our experimental model, small amounts of ions or particles may have been released from implanted titanium or nickel wire, helping induce biological responses to implanted wires.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to titanium particles, titanium ions also enhance immunoreactivity. Titanium ion exposure enhances proinflammatory cytokine production in macrophages via activation of NLRP3 or NF-κB 11,12) . Other studies showed that titanium ions also decrease the viability and inhibit the differentiation of osteoblastlike MC3T3-E1 cells 13) .…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these is recognized as a common event induced by all the NLRP3 inflammasome stimuli (21,25). To date, studies on metal-activated inflammasomes have mainly focused on the NLRP3 inflammasome (26,27). Details of these studies are discussed in the following sections and are summarized in Figure 2.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%